The Effect of the Image of Destinations on Household Income and Distribution: Evidence From China’s Tourist Cities - Xu, Sheng; Zhang, Yunzhi; Yin, Jinghua; Huang, Guan (Frontiers in Psychology, 2022)
This paper examines the effect of the image of destinations on the wage income of resident households, and the corresponding income inequality, from a novel perspective. This work uses China’s excellent tourism city image program, which is an urban planning policy implemented by the central government across cities to enhance the image of the city destination in the minds of tourists, and then promote tourist motivation and local tourism development to assess the effect on household wage income and its distribution. Results show that the program significantly increases household wage income by increasing employment opportunities, promoting business and population agglomeration, and improving urban infrastructure. Additionally, the image of the city destination promotion causes an increase in income inequality among households.